The face of the next leader: The role of facial structure and perceptions of trustworthiness on CEO selection - GOMULYA, David (Institutional Knowledge at Singapore Management University, 2015)
Research on CEO succession indicates that CEO characteristics that signal competence are valued during the CEO selection process. However, less is known about the role of perceptions of trustworthiness when selecting a successor CEO. We investigate a situation in which the trustworthiness of the CEO successor may be critically important to the firm - when the firm has been shown to have engaged in financial misconduct in the past. Drawing on prior research, we argue that perceptions of trustworthiness are influenced by facial appearance, which, in turn, affects CEO selection and reactions to CEO announcements. In an archival study of firms that have announced financial restatements, we find that trustworthy-looking individuals are indeed more likely to be selected as successors and that these individuals are more favorably perceived by external observers.